Examining Nigeria's political structure (NPS) as a vehicle for criminality, corruption and anti-national development - Dominic, Egede Dominion; Mahamed, Mastura; Uwadiegwu, Inyama Victor (Human Resource Management Academic Research Society, 2023)
This study intends to develop a standard political structure in the Nigerian context that is national, economic, and social-political development oriented. Again, this study contributes to the deficiencies in the past literature on political science regarding political structure and good governance. There is a global paradigm shift in the citizens' acceptability of political decisions and promises, especially in Nigeria. The concept of emilokanism is an anti-democratic political structure. The downscale of citizens' trust in the government keeps decreasing. The U.S. citizens' trust in government dropped from 77% in the 1960s to 54% in 2001 and then went down to 17% in 2019. However, European and Asian countries are not left out. Nigeria is not exceptional in this drop in government trust among citizens due to the so-called political structure. Nigerian Leaders are the viruses eating deep into the mechanism and framework of the country. The cost of running a corrupt government is much higher than running a corrupt-free nation. In this article, the authors employed a scoping review of studies on political studies, political structure, good governance, political corruption, and politics to demystify the repulsive nature of political structure in Nigeria and provide recommendations for a more refined architecture. The findings revealed that one of the significant reasons for corruption among Nigerian political leaders is the political structure. Nigeria's political system gives room for corruption and thereby economically enslaves her citizenry.